Imago Dei and human rights protections of forced migrants: A North Korean case study. Issue 1 (13th January 2020) - Yoon, I Sil
Abstract: In this article, I examine the significance of the theological concept of Imago Dei in recognizing the dignity of North Koreans and in necessitating socio‐structural transformation for their human rights protections in South Korean society. North Koreans residing in South Korea are an example case of forced migrants who experience mistreatment and discrimination in their destination country. In this reality, the concept of Imago Dei can call South Koreans to recognize North Koreans' dignity. It can further criticize South Korea's social structure that intensifies North Koreas' maladjustment in South Korean society, and necessitate institutional levels of transformation.